Аппроксимация ограниченного решения линейного разностного уравнения на Z² решениями соответствующих краевых задач в банаховом пространстве - Городний, М.Ф. (Український математичний журнал, 1995)
Досліджено питання про існування і єдиність розв'язків крайових різницевих задач у банаховому просторі, відповідних одному різницевому рівнянню на Z². Доведено теорему про наближення єдиного обмеженого розв'язку розглядуваного рівняння розв'язками відповідних крайових задач. We study the problem of existence and uniqueness of solutions of boundary-value difference problems in a Banach space that correspond to a certain difference equation on Z². We prove a theorem on approximation of the unique bounded solution of the considered equation by solutions of the corresponding boundary-value problems.